The role and function of thermal insulation in architecture - Nafici .N; Zain .M.F.M (Penerbit UKM, 2011)
With movement of cities toward a more industrial urban structure, they need of green environment is increasing. One of the solutions is creating the green roofs which the interest on them is increasing. However, having a green roof requires some technical guidelines to provide the desired environment. The technical guidelines for instruction of green roof aim to provide an adapted, environmental friendly and suitable material for offering the optimal operation. This focus of this document is mainly on the technical aspects of the material in need for insulation,